2022
DOI: 10.1007/s00330-022-08868-3
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced mammography for the assessment of screening recalls: a two-centre study

Abstract: Objectives To evaluate the potential of contrast-enhanced mammography (CEM) for reducing the biopsy rate of screening recalls. Methods Recalled women were prospectively enrolled to undergo CEM alongside standard assessment (SA) through additional views, tomosynthesis, and/or ultrasound. Exclusion criteria were symptoms, implants, allergy to contrast agents, renal failure, and pregnancy. SA and CEM were independently evaluated by one of six radiologists, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Overall, the findings by Cozzi et al [5] confirm results from previous studies that CEM has the potential as a problemsolving tool for the assessment of screening recalls [6]. A practical advantage is the short learning curve as demonstrated by increased diagnostic accuracy even for less experienced radiologists [6].…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Overall, the findings by Cozzi et al [5] confirm results from previous studies that CEM has the potential as a problemsolving tool for the assessment of screening recalls [6]. A practical advantage is the short learning curve as demonstrated by increased diagnostic accuracy even for less experienced radiologists [6].…”
supporting
confidence: 80%
“…In this issue of European Radiology, Cozzi et al [5] present the effect of CEM on biopsy rate in women recalled for assessment after DM screening. The study included 207 women with 225 suspicious findings prospectively enrolled to undergo CEM alongside standard assessment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Digital mammography (DM), which uses a 2D technique, is a widely used tool for detecting breast cancer, and the American Cancer Society has declared that mammography is one of the best approaches to preserving women's health (Lei et al 2019;Wanders et al 2022). However, mammography still has a serious restriction in that the appearance of lesions may be diminished, leading to missed or incorrect diagnosis for relying exclusively on a morphological appraisal of suspicious ndings, which may foster an increase in the positive predictive value (PPV) of work-up examinations (Hui et al 2020;Cozzi et al 2022). Radiomics, which uses quantitative methods that can be more bene cial for diagnosing and de ning benign and malignant breast tumors, was used to overcome these constraints (Erdim et al 2020;Priya et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the American College of Radiology practice parameters underline how any facility performing breast MRI should provide MRI-guided biopsy whenever needed, or at least cooperate with a referral centre capable of performing it. While a recent study [8] pitching the standard morphological work-up of screening recalls against a CEM-only approach found that rates of CEM-only findings match those observed for MRI, another study [9] had already highlighted how only 31% of CEM-detected findings had a correlate at second-look ultrasound, emphasizing the need of CEM-guided biopsy.…”
mentioning
confidence: 99%